Powered Rhinoplasty: A Simple Step-by-Step Approach. Issue 1 (24th December 2020) - Racy, Emmanuel; Fanous, Amanda; Benmoussa, Nadia
Abstract : Summary: Reduction of a nasal hump and nasal base narrowing are very common steps during a primary rhinoplasty procedure. The greatest difficulty is to obtain stable fracture lines, a natural appearance, beautiful dorsal aesthetic lines, and the absence of palpable or visible irregularities, especially in the long term. The surgeon strives for a reproducible technique, which seems to be more feasible with mechanical osteotomies (powered or piezoelectric) than with traditional manual osteotomies. The aim of this article is to describe powered osteotomy in a step-by-step fashion to provide a clear guideline for rhinoplasty surgeons.